IMPLEMENTASI PROFESI BIDAN SEBAGAI PENGUATAN PARTISIPASI PEREMPUAN DALAM BELA NEGARA - Nimas Agnissa Jihand Swastikani Prapsetyo; Kiki Lestari; Agung Prapsetyo (PPM Sdirjianbang Akademi Militer, 2023)
According to the 1945 Indonesian Constitution, Article 30 paragraph 1; Everyone has the right and obligation to defend the country. Likewise, those who work as midwives also have the right and obligation to defend the country. The problem is how can people who work as midwives participate in defending the country? The purpose of this research is to find out the implementation of the midwifery profession as strengthening women's participation in defending the country. The research method uses descriptive qualitative methods and literature studies in data collection. The results of the study show that the midwifery profession is one of the National Resources for National Defense, where a professional midwife will assist in the birth of healthy nation's children as potential successors to the Indonesian nation. The implementation of the Midwife Profession in active participation in efforts to defend the country is by becoming a midwife who is professional in her field and upholds human values ​​and religious norms, whereas according to RI Law no. 23 of 2019, as Indonesians who work as midwives participating in defending the country can be achieved by: 1) registering to become a TNI soldier as a Main Component; 2) register to become a Reserve Component ready to be mobilized; and 3) become a professional as a Supporting Component.